Polkvantitativno modeliranje kot podpora učenja z računalnikom - Slanc, Radovan (Uporabna informatika (Ljubljana), 1996)
The paper sddresse the possobility of building and testing a model, and thereby confirming, increasing, or revising our knowledge, all of which are elements of a learning process. Two examples of semi-quantitative models are presented in the paper, explaining the approach of implementing semi-quantitative models that allow model testing without particular values ofparameters at the same time, which is a requirement in quantitative modelling.
Keywords: polkvantitativno modeliranje; preizkušanje modelov; računalnik; učenje